2004
DOI: 10.1152/ajpheart.00228.2004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of oxidized LDL-induced collagen secretion by graft and aortic SMCs: role of PDGF

Abstract: Smooth muscle cells (SMCs) from prosthetic vascular grafts constitutively secrete higher levels of collagen than aortic SMCs. Lipid oxidation products accumulate in grafts, and we postulated that they stimulate SMC production of collagen. The effect of oxidized low-density lipoprotein (oxLDL) on type I collagen secretion by aortic and graft SMCs was compared. SMCs isolated from the canine thoracic aorta or Dacron thoracoabdominal grafts (n = 10) were incubated with native LDL or oxLDL (0-400 microg cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…34 LY83583-induced superoxide production, but not H 2 O 2 , increases procollagen a1 (I) mRNA levels in canine aortic smooth muscle cells, which suggests that superoxide anion regulates gene expression. 35 Our results that LY83583 treatment reduced both MYPT1 mRNA and protein levels in HASMCs are consistent with this notion. Furthermore, the attenuation of LY83583-reduced MYPT1 protein levels by the co-treatment with a membranepermeable SOD strongly implicates a role for superoxide anion in MYPT1 reduction.…”
Section: Discussionsupporting
confidence: 88%
“…34 LY83583-induced superoxide production, but not H 2 O 2 , increases procollagen a1 (I) mRNA levels in canine aortic smooth muscle cells, which suggests that superoxide anion regulates gene expression. 35 Our results that LY83583 treatment reduced both MYPT1 mRNA and protein levels in HASMCs are consistent with this notion. Furthermore, the attenuation of LY83583-reduced MYPT1 protein levels by the co-treatment with a membranepermeable SOD strongly implicates a role for superoxide anion in MYPT1 reduction.…”
Section: Discussionsupporting
confidence: 88%
“…6 Oxidized low-density lipoprotein (oxLDL) also stimulates SMC growth factor production by ECs, 7 is chemotactic for SMCs, 8 stimulates SMC proliferation, 9 and enhances SMC production of collagen. 10 These properties adversely affect vascular graft healing.…”
mentioning
confidence: 99%
“…Nevertheless there is a reported negative effect on human arterial smooth muscle cells [Okada et al, 1993]. The recent study by Absood et al [2004] showed that PDGF caused increased collagen production by synthetic smooth muscle cells but not by contractile smooth muscle cells. The oxLDL induced increase in collagen production was blunted by the addition of anti-PDGF antibody, suggesting that PDGF mediated the stimulation of collagen synthesis.…”
Section: Cellular Growth Factors and Their Influence On Collagen Syntmentioning
confidence: 99%
“…In a study conducted by Absood et al [2004], it is reported that oxidized LDL and superoxide generator LY-83583 induce higher level of collagen synthesis in graft and aortic smooth muscle cells. Superoxides are known to stimulate collagen synthesis by hepatocytes and fibroblast in vitro [Hussain et al, 1987;Chandrakasan and Bhatnagar, 1991].…”
Section: Miscellaneous Factors That Influence Collagen Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation